Regional trade agreements versus global trade liberalisation : implications for a small island developing state - Asafu-Adjaye, John (2009)
Employs a dynamic computable general equilibrium (CGE) model of the Fijian economy to investigate the comparative effects of two key strategies for trade liberalisation, namely, a regional trade agreement versus global trade liberalisation.